EFFORTS OF PRABUMULIH 5 PRIVATE VOCATIONAL SCHOOL IN INSTRUDING RELIGIOUS MODERATION ACCORDING TO THE “FRIENDLY” MOTTO (RELIGIOUS, AMANAH, INDEPENDENT, SAFE, HARMONIC) - Mirnawati, Mirnawati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Religious moderation is an effort to understand and assure all who have a religion to carry out their activities according to their beliefs. Religious moderation reflects a person's success and the scope of a nation with a culture of tolerance and a healthy environment in society. Because religion is a sensitive matter, that becomes the most significant conflict material in the community outside of other factors. This study aimed to find out and describe the inculcation of religious moderation in SMPN 5 Prabumulih through the motto FRIENDLY. SMPN 5 Prabumulih carries out these efforts, so indirectly, they have carried out the function of their slogan, namely FRIENDLY, where the religious part is reflected in the religious activities provided by the school; the mandate function is to realize the needs of Muslim and non-Muslim students according to reality without any difference, the independent part is that the school gives students the freedom to take a stand in studying their respective religions. In contrast, for the safe function, the school provides a sense of security and comfort for all students to practice their religion in the school environment. For a harmonious process, namely, the school offers education character in students and teachers as well as all parties of SMPN 5 Prabumulih to have values and morals as educated citizens who look after each other, provide a sense of security and tolerance, not be racist or limit the movements of those who are in the minority.